Diagnosis of Hairy Cell Leukemia and HCL-like Disorders: Pitfalls to Avoid and the need to Integrate Molecular Data - Troussard, Xavier; Kerneves, Pauline; Maitre, Elsa (Archives of Clinical and Medical Case Reports, 2022)
The diagnosis of Hairy Cell Leukemia and HCL-like diosrders, including HCL variant (vHCL) and Splenic Diffuse Red Pulp Lymphoma (SDRPL), is based on the examination of the peripheral blood and bone marrow smears allowing the identification of hairy cells and the flow cytometric analysis. The immunologic scoring system, based on the reactivity with each of the four markers (CD11c+, CD25+, CD103 and CD123), usually ranges from 4 (typical of HCL) to 0 (HCL-like disorders). HCL is sometimes confused with other HCL-like disorders. Differentiating all the entities may be challenging due to overlapping features, particularly morphologic and immunophenotypic criteria. Unusual and atypical immunophenotypes are frequently observed: the clinical impact of this variability, if it does exist, remains to demonstrate. In a large cohort of patients, we found a CD103 expression, which was heterogeneous and found only in a fraction of hairy cells in 2/68 cases (3%). We also identified CD5 and CD10 expression in 7/68 (10%) and 12/68 (18%) cases, respectively. Looking for the genetic alterations is crucial: the BRAFV600E mutation was detected in 80-90% of HCL. In cases with BRAF wild type (BRAFWT), the possibility of alternative mutations particularly in exon 11 should be excluded. Conversely to HCL, the BRAFV600E mutation was never identified in HCL-like disorders. Activating mutations in MAP2K1 gene (15q22.1-q22.3) were identified in half of the cases. Recurrent hotspot mutations of U2AF1 encoding a protein belonging to the spliceosome were detected in 15% of vHCL. Twenty-four per-cent of patients with SDRPL presented mutations in CCND3 and/or recurrent mutations or losses in BCOR (gene encoding the BCL6 corepressor). There is no known molecular data in jpHCL. Atypical morphologic and immunophenotypic profiles are frequent and the use of genetic data could be offer a new posssibility for a better classification of HCL and HCL-like disorders.